ROLE OF METFORMIN IN POLYCYSTIC OVARIAN SYNDROME - Wahab, Samdana; Zahoor, Farnaz; Karim, Rukhsana (Journal of Postgraduate Medical Institute, 2013)
Objective: To assess the role of Metformin in Polycystic ovarian syndrome (PCOS). Methodology: This interventional, quasi-experimental study was conducted at Department of Obstetrics &Gynaecology, Lady Reading Hospital Peshawar from October 2004 to October 2006. A total of 35 patientswith PCOS were included fulfilling Rotterdam Criteria. Metformin was given in a dose of 850 mg twice aday. Patients' reassessment was done clinically on a three monthly basis while laboratory investigationsand Transvaginal scan was done after two years. Data was analysed using SPSS v. 16. Results: The mean age of the sample was 27+5.2 years. Out of 35, 29(82.8%) had primary infertility while6(17.2%) had secondary and only 7(20%) of those conceived. Menstrual irregularities were present in30(85.7%) patients, 27(55.5%) with oligomenorrhea, 2(5.7%) with amenorrhea and 1(2.86%) withpolymenorrhea. Out of these 15, 2 and 1 showed improvement, respectively. Regarding hyperandrogenism,22(62.8%) patients were with hirsutism, 3(9.4%) had acne and 10(28.5%) had hair loss. Out of these 0, 2and 3 improved, respectively. Transvaginal scan showed polycystic ovaries in all patients at baseline whilethe cysts dissolved in 15(42.8%) patients. Biochemical investigations like Leutinizing Hormone:FollicleStimulating Hormone(LH:FSH), Serum Testosterone, Serum Prolactin, Random Blood Sugar(RBS) andSerum Insulin was raised in 32(91.4%), 24(68.5%), 9(25.7%), 3(8.5%) and 10(28.5%) patients respectivelyand 17(53.1%), 13(54.2%), 4(44.4%), 1(33.3%) and 4(40%) patients improved respectively. Conclusion: Metformin is an effective drug to improve the menstrual irregularities, LH:FSH and serumtestosterone but it does not show improvement in clinical signs and symptoms of hyperandrogensim.